Investigation of the formation of complexes between selected organic compounds and the chlorides and sulphates of chromium - Ellis, Melville John (Rhodes University, Faculty of Science, Department of Chemistry, 1961)
Some properties of soluble chromium complexions containing coordinated aliphatic acids have been studied. The work falls naturally into two sections. In the first, the coordination of a series of âŠ„, Î² andâŠ amino acids by chromium chloride has been studied by physical methods. The tanning action of chromium chloride in the presence of these amino acids has also been studied. The absorption spectra of the complexes were similar to those reported previously for trivalent chromium solutions, having two pronounced maxima in the visible region. From the variations in these absorption maxima, it is suggested that the absorption maximum in the 580 m u region is influenced by coordination of the chromium with the ligand, while the maximum in the 420 m u region is also affected by the olation of the basic chromium salts. The spectrophotometric evidence indicates that raising the pH or the concentration of the ligand in the solution increases the amount of coordination, and further, that the tendency for coordination increases as the hydrocarbon chain separating the carboxyl and amino groups becomes longer. This suggests that tho stability of the complex is not dependent on chelate ring formation, but is influenced by the pKâ‚ value of the carboxyl group of the . ligand. Potentiometric titrations support the hypothesis that only the carboxyl group is coordinated, to an extent depending on its pKâ‚ value, since the curves have shown that the amino group is still free to titrate. Paper electrophoresis has shown that all the complexes prepared were cationic, indicating that the amino acids were coordinated as dipolar ions. The tanning action of the masked chromium solutions has confirmed the deductions made from the physical measurements. Increasing the amount of amino acid added to the solution lowered the chromium fixation and the hydrothermal stability of the leather, and further, that for solutions at the same pH containing the same amount of masking agent, tanning action was least for the âŠ amino acid and greatest for the âŠ„ amino acids. Comparison of the present data with the corresponding results obtained with chrome alum solutions showed that coordination of the amino acids was greater in the case of the chromium chloride solutions. The second section of the experimental work was an investigation of the coordination of substituted acetic and propionic acids by chromium chloride and chromium sulphate. Spectrophotometric and potentiometric methods were applied and the various solutions were also used in miniature tanning experiments. Certain difficulties were encountered in the preparation of some of the complexes, and it was not possible to carry the work to a point where conclusive results could be obtained. Nevertheless, the work reported suggests that chelate ring formation occurs in the coordination of hydroxy-carboxylic acids, resulting in exceptionally high stability of the complex. In the case of the other ligands, containing amino, chloro and bromo groups, as well as with acetic and propionic acids, the results suggest that coordination involves the carboxyl group only, and that the pY value of this group is an important factor determining the stability of the complexes.
Keywords: Organic compounds; Chromium compounds; Chlorides; Sulfates